Monitoramento da expressão gênica de Xanthomonas axonopodis pv. citri em diferentes condições ambientais - Defina, Tânia Paula Aquino [UNESP] (2003)
The bacterium Xanthomonas axonopodis pv. citri is a pathogen causing citric canker that compromises part of the orange production in the State of São Paulo, with negative consequences for the economy of the State and the Country. For the future control of citric canker, several investigators participated in the Xanthomonas Genome Project in order to determine the gene set of this bacterium and to contribute to the identification of the genes involved in its pathogenicity. In this respect, the objective of the current study was to monitor the gene expression of the pathogen when submitted to different environmental conditions such as variation in extracellular pH, and to different antibacterial agents using Differential Display RT-PCR. Using this method we obtained the expression of important genes when the bacteria were submitted to pH 8.0, such as a gene related to an MFS transporter, valine-pyruvate aminotransferase, glucan 1,4--glucosidase and a conserved hypothetical protein. When submitted to the action of inhibitory agents such as ampicillin, Xanthomonas expressed various proteins, i.e., integrase, virulence protein and a phosphoribosylformylglycinamide cycloligase. In a culture containing penicillin, the bacteria expressed the gene of tyrosyl t-RNA synthetase. There is great interest in determining the mechanisms of attack of Xanthomonas axonopodis pv. citri, its interaction with plants and also the strategies it uses to inhibit the defense system of the host, promoting the onset of the disease. In this respect, the present results, added to those obtained in other functional projects, are expected to provide information about the defense mechanism of Xanthomonas and about the plant-bacterium interaction in order to contribute to the control of citric canker